Efficiency enhancement in orange red thermally activated delayed fluorescence OLEDs by using a rigid di-indolocarbazole donor moiety. (October 2021) - Maeng, Jee Hyun; Braveenth, Ramanaskanda; Jung, Young Hun; Hwang, Soon Jae; Lee, Hyuna; Min, Hye Li; Kim, Jun Yun; Han, Chang Wook; Kwon, Jang Hyuk
Abstract: The development of orange-red thermally activated delayed fluorescence (TADF) materials with good optoelectronic and electroluminescence properties are full of challenges due to limited molecular designs. Herein, we investigated a series of materials using dimethylacridine (DMAC) and diindolocarbazole (DI) donor with dibenzo [a, c] phenazine (DBP) acceptor, and compared the characteristics of all synthesized materials as emitters. Due to lower singlet energy level, the rate constant of internal conversion (kIC ) contribute to nonradiative decay cannot be ignored at the orange-red region. Therefore, employing rigid donor and acceptor moieties play a major role in suppressing kIC . We observed that employing a rigid donor of DI at β position enhanced the PLQY of 96.1% when compared to acridine based emitters. 5-(dibenzo [a, c] phenazin-11-yl)-10, 15-diphenyl-10, 15-dihydro-5H-diindolo [3, 2-a:3′, 2′-c] carbazole (β-DI-DBP) based OLED device showed better current efficiency (CEmax ) of 47.1 cd/A and maximum external quantum efficiency (EQE) of 23.8%. This work demonstrates a better approach towards high PLQY orange red TADF material development. Highlights: A series of orange-red TADF emitters were developed using dibenzo phenazine (DBP) acceptor. Employing rigid donor and acceptor moieties play a major role in suppressing kIC . Rigid donor of DI at β position enhanced the PLQY up to 96%. OLED device showed maximum external quantum efficiency (EQE) of 23.8%.